Pendampingan Implementasi Pelaporan Keuangan SAK ETAP Di Koperasi Inti Dana Semarang - Ayu Miranti Kusumaningrum; Bambang Widjanarko Susilo; Edy Susanto; Galuh Aninditiyah; Zarah Dinul Khaq; Vivi Kumalasari Subroto; Nanik Qosidah; Benny Cuaca (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Savings and loan cooperatives play an important role in strengthening the community's economy, especially in the micro and small sectors. However, many cooperatives face various challenges related to proper financial management and recording. Limited human resources and lack of understanding of relevant accounting standards are the main obstacles. This community service aims to increase understanding and application of SAK ETAP (Financial Accounting Standards for Entities Without Public Accountability) in the Koperasi Simpan Pinjam (KSP) Inti Dana Semarang. The methods used include training, mentoring, and evaluation of the implementation of SAK ETAP. The results of this program show an improvement in the quality of financial reports and transparency in cooperative management. This initiative has a positive impact on member trust and the sustainability of cooperative businesses